Agreement between photographic and clinical examinations in detecting developmental defects of enamel in infants. (7th April 2013) - Chen, Yao; Lee, Wonik; Ferretti, Gerald A.; Slayton, Rebecca L.; Nelson, Suchitra
Abstract: Objectives: This study assesses the reliability of photographic method with clinical examinations in detecting developmental defects of enamel (DDE) in the anterior primary teeth of infants. Methods: The study sample was a part of an ongoing longitudinal study to assess risk factors for early childhood caries, and consisted of 138 and 238 infants who had scheduled follow‐up visits at approximately 8 and 18‐20 months corrected age, respectively. The modified DDE Index was used to record enamel defects (opacity, hypoplasia, and all types of defects) on anterior primary teeth by trained dentist examiners. Photographs of the teeth were taken using a digital camera. Statistical analysis included Cohen's Kappa for reliability, and McNemar test and paired t ‐test for comparison between photographic and clinical examinations. Results: The level of agreement between clinical and photographic methods was fair to moderate with Kappa values ranging from 0.252 to 0.514. The photographic examination detected significantly more DDE than the clinical examination regardless of age group and type of DDE. The intra‐ and inter‐examiner reliability of the photographic method was excellent with Kappa values ranging from 0.638 to 0.927. Conclusions: Within the limitation of this study, the photographic method can be a sound approach for verifying the diagnosis of DDE.